2009
DOI: 10.1002/app.29456
|View full text |Cite
|
Sign up to set email alerts
|

Crosslinking reactions of oxidized cellulose fiber. II. Reactions between dialdehyde cellulose and chito‐oligosaccharides on lyocell fabric

Abstract: Antimicrobial nonfibrillated lyocell fibers were developed by crosslinking reactions between dialdehyde cellulose and chito-oligosaccharides. Partially oxidized lyocell fibers with sodium metaperiodate were successfully crosslinked with two water-soluble chito-oligosaccharides with different molecular weights by Schiff base formation and were reduced with sodium borohydride. Infrared spectroscopy measurements showed the characteristic absorption bands caused by the functional groups of each reaction product. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 31 publications
0
7
1
Order By: Relevance
“…Antibacterial activity of chitosan-coated Lyocell fibers against Escherichia coli and Staphylococcus aureus was confirmed by in vitro experiments. Effectiveness was found to be higher with increasing chitosan molecular weight, in contrast to Han's results (Han and Lee, 2009).…”
Section: Schiff Base Reactionscontrasting
confidence: 85%
See 2 more Smart Citations
“…Antibacterial activity of chitosan-coated Lyocell fibers against Escherichia coli and Staphylococcus aureus was confirmed by in vitro experiments. Effectiveness was found to be higher with increasing chitosan molecular weight, in contrast to Han's results (Han and Lee, 2009).…”
Section: Schiff Base Reactionscontrasting
confidence: 85%
“…A disadvantage of periodate oxidation approaches is that they open some of the glucose rings of the polysaccharide main chain, reducing chain rigidity, reducing molecular weight (by oxidation side reactions and by instability of the oxidized products), and by introducing possibly undesired reactivity. Han et al reported crosslinking reactions between dialdehyde cellulose and chitooligosaccharides (Han & Lee, 2009;Han, Lee, & Kim, Fig. 2.…”
Section: Schiff Base Reactionsmentioning
confidence: 99%
See 1 more Smart Citation
“…DAC is amenable to a whole range of reactions from modification with small aliphatic [417] or aromatic [418] amines to reacting with amino-functionalized biopolymers including collagen [419] and chitosan. [420,421] Such reactions are mainly based on Schiff base reactions. [422,423] Cross-linked DAC have been used in a wide range of applications, for example, as an adsorbent of dyes, [424,425] heavy metals [426,427] and DNA, [428] protein immobilization, [429,430] chromatography, [418] nanoparticle carries, and drug delivery.…”
Section: Mechanochemical Production Of Dialdehyde Cellulosementioning
confidence: 99%
“…In principle, DAC is amenable to the whole range of reactions and derivatizations known fora ldehydes from organic chemistry textbooks. DAC can be modified with small aromatic [6] or aliphatic amines, [7] and can also react with amino-functionalized biopolymers, such as chitosan [8,9] and collagen. [10] These modifications are mostly based on Schiff base reactions.…”
Section: Introductionmentioning
confidence: 99%